Public higher education financing in the Republic of Moldova - MANOLE, Tatiana (Journal of Social Sciences, 2019)
This article investigates the new mechanism of higher education financing in the Republic of Moldova. This mechanism is based on the principle of differentiating the budgetary allocations according to the complexity of the study programs. The differentiation is based on distinct adjustment coefficients, which in fact are underlying the determination of the „standard per unit equivalent student cost”. We consider it an important step in financing higher education, which will differentiate the way of financing depending on the complexity of specialists' education for the country’s economy.